2013
DOI: 10.1016/j.ophtha.2013.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Amblyopia or Strabismus in Asian and Non-Hispanic White Preschool Children

Abstract: Objective To determine the age- and race-specific prevalence of amblyopia in Asian and non-Hispanic white children aged 30 to 72 months and of strabismus in children aged 6 to 72 months. Design Cross-sectional survey. Participants A population-based, multiethnic sample of children aged 6 to 72 months was identified in Los Angeles and Riverside counties in California to evaluate the prevalence of ocular conditions. Methods A comprehensive eye examination and in-clinic interview were conducted with 80% of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
187
4
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 258 publications
(218 citation statements)
references
References 40 publications
(37 reference statements)
8
187
4
1
Order By: Relevance
“…The questions were answered mostly by the parents. Its structure was similar to the design of the questionnaire used previously in the Refractive Error Study in Children (RESC) and the Multi-Ethnic Pediatric Eye Disease Study [7,11]. …”
Section: Methodsmentioning
confidence: 99%
“…The questions were answered mostly by the parents. Its structure was similar to the design of the questionnaire used previously in the Refractive Error Study in Children (RESC) and the Multi-Ethnic Pediatric Eye Disease Study [7,11]. …”
Section: Methodsmentioning
confidence: 99%
“…[1][2][3][4] These deficits often lead to reduced or absent stereoacuity when assessed with current clinical methods. At the same time, qualitative work has shown that even in the absence of clinically measurable stereopsis, the experience of compelling 3D volumetric depth is reported when viewing dynamic stereoscopic stimuli such as 3D video.…”
Section: Introductionmentioning
confidence: 99%
“…9,10 The prevalence of strabismus ranges from less than 0.5% to about 5% in different communities and countries. 6,[11][12][13][14][15][16][17][18][19][20][21][22][23][24][25] However, the prevalence is substantially higher in some diseases, such as Down or Marfan syndrome. 21,26 Available population-based studies on strabismus have mostly addressed binocular vision problems besides amblyopia and very few studies have exclusively evaluated strabismus.…”
Section: Introductionmentioning
confidence: 99%
“…21,26 Available population-based studies on strabismus have mostly addressed binocular vision problems besides amblyopia and very few studies have exclusively evaluated strabismus. 6,[11][12][13][14][15][16][17][18][19][20][21][22][23][24][25] One of the most important questions about strabismus is the ratio of esotropia to exotropia, which is different in different countries. Although most studies have reported that esotropia is more prevalent, most strabismic patients have exotropia in East Asian countries.…”
Section: Introductionmentioning
confidence: 99%